The Milky Way educational and support programme: Structure, content and strategies. Issue 4 (August 2016) - Meedya, Shahla; Fahy, Kathleen; Parratt, Jenny A.
Abstract: Background: Health professionals have put much effort into supporting women to continue breastfeeding up to six months and beyond. The majority of those efforts have not been successful for primiparous women. Primiparous women who engaged in the Milky Way Programme had an improvement in breastfeeding rates of almost 50% at six months when compared to women in a control group. Purpose: To provide details of the Milky Way Programme including the educational structure, content and strategies as well as the process of postnatal telephone support. Overview: The details of the Milky Way Programme are presented including a summary of literature review that was used to design the programme. The structure and content of the programme is then presented. Finally, the strategies with some practical examples are outlined in more detail. Conclusion: The programme is evidence-based, theoretically informed and woman-centred. This paper provides the necessary information to health professionals who are trained to educate and support breastfeeding women to implement similar programmes in their workplaces.